Effectiveness of a 5-year school-based intervention programme to reduce adiposity and improve fitness and lifestyle in Indian children; the SYM-KEM study. Issue 1 (29th September 2015) - Bhave, Sheila; Pandit, Anand; Yeravdekar, Rajiv; Madkaikar, Vaishali; Chinchwade, Trushna; Shaikh, Nasreen; Shaikh, Tasneem; Naik, Shraddha; Marley-Zagar, Ella; Fall, Caroline H D
Abstract : Design: Non-randomised non-blinded school-based intervention study. Setting: Two schools in the cities of Pune and Nasik, India. Participants: The intervention group comprised children attending a Pune school from 7–10 years until 12–15 years of age. Two control groups comprised children of the same age attending a similar school in Nasik, and children in the Pune intervention school but aged 12–15 years at the start of the study. Intervention: A 5-year multi-intervention programme, covering three domains: physical activity, diet and general health, and including increased extracurricular and intracurricular physical activity sessions; daily yoga-based breathing exercises; making physical activity a 'scoring' subject; nutrition education; healthier school meals; removal of fast-food hawkers from the school environs; and health and nutrition education for teachers, pupils and families. Main outcome measures: Body mass index (BMI), waist circumference, physical fitness according to simple tests of strength, flexibility and endurance; diet; and lifestyle indicators (time watching TV, studying and actively playing). Results: After 5 years the intervention children were fitter than controls in running, long jump, sit-up and push-up tests (p<0.05 for all). They reported spending less time sedentary (watching TV and studying), more time actively playing and eating fruit more often (p<0.05). The intervention did not reduce BMI or the prevalence of overweight/obesity, but waist circumference was lower than in the Pune controls (p=0.004). Conclusions: It was possible to achieve multiple health-promoting changes in an academically competitive Indian school. These changes resulted in improved physical fitness, but had no impact on the children's BMI or on the prevalence of overweight/obesity.